Determining the Productive Energy of Soybean Meal Relative to Corn and Feed-grade Amino Acids - Ty Kim; Ethan B. Stas; Jessica L. Smallfield; Hilario M. Cordoba; Mike D. Tokach; Robert D. Goodband; Joel M. DeRouchey; Jason C. Woodworth; Jordan T. Gebhardt; Keith D. Haydon (Kansas Agricultural Experiment Station Research Reports, 2024)
A total of 2,153 finishing pigs (PIC 337 × 1050; initially 63.6 ± 1.03 lb) were used in a 112-d growth study to determine the productive energy of soybean meal (SBM) relative to corn and feed-grade amino acids. Pens of pigs were blocked by initial BW and allotted to one of four dietary treatments in a randomized complete block design. There were 26 or 27 pigs per pen and 20 pens per treatment across two barns. Soybean meal NE value used in diet formulation was 947 kcal/lb (78% NE of corn; NRC, 2012). The four treatments consisted of a diet containing a low level of SBM and added feed-grade amino acids (Low SBM), and three diets with a 3.37 (Med-Low SBM), 6.69 (Med-High SBM), and 10% (High SBM) increase in SBM compared to the Low SBM diet and decreased feed-grade amino acids. The High SBM diet did not contain feed-grade L-lysine. Treatment diets were fed in four phases. Pigs were weighed and feed disappearance was measured every 14 d to determine ADG, ADFI, F/G, and caloric efficiency (CE). From d 0 to 56, increasing SBM decreased (linear, P < 0.05) ADG and ADFI, with no effect on F/G. From d 56 to 112, increasing SBM tended (linear, P < 0.10) to decrease ADG but there was no effect on ADFI. As a result, F/G worsened (linear, P = 0.050) as dietary SBM increased. From d 0 to 112, there was a decrease (linear, P < 0.05) in ADG and ADFI as SBM level increased, but there was no effect on F/G. Caloric efficiency improved (linear, P < 0.05) as SBM level increased, suggesting a greater NE concentration than initially estimated. Increasing SBM decreased (linear, P < 0.05) carcass ADG and worsened (linear, P < 0.05) carcass F/G, but there was no effect on carcass CE. Increasing SBM decreased (linear, P < 0.05) HCW and carcass yield. Backfat depth and percentage lean were lowest and greatest, respectively, (quadratic, P < 0.05) for pigs fed the intermediate SBM levels. There was an increase (linear, P < 0.05) in pig removals with increasing SBM but no treatment effect on mortality. However, when combined, removals and mortality were increased (linear, P < 0.05) as SBM level increased. The results of this study suggest that when using caloric efficiency, SBM is estimated to contain 93.5% on a liveweight basis or 83.9% on a carcass weight basis of the NE of corn.
Keywords: caloric efficiency; finishing pigs; growth; net energy; soybean meal